Comprehensive systematic review summary: Treatment of cerebellar motor dysfunction and ataxia. (6th March 2018) - Zesiewicz, Theresa A.; Wilmot, George; Kuo, Sheng-Han; Perlman, Susan; Greenstein, Patricia E.; Ying, Sarah H.; Ashizawa, Tetsuo; Subramony, S.H.; Schmahmann, Jeremy D.; Figueroa, K.P.; Mizusawa, Hidehiro; Schöls, Ludger; et al.
Abstract : Objective: To systematically review evidence regarding ataxia treatment. Methods: A comprehensive systematic review was performed according to American Academy of Neurology methodology. Conclusions: For patients with episodic ataxia type 2, 4-aminopyridine 15 mg/d probably reduces ataxia attack frequency over 3 months (1 Class I study). For patients with ataxia of mixed etiology, riluzole probably improves ataxia signs at 8 weeks (1 Class I study). For patients with Friedreich ataxia or spinocerebellar ataxia (SCA), riluzole probably improves ataxia signs at 12 months (1 Class I study). For patients with SCA type 3, valproic acid 1, 200 mg/d possibly improves ataxia at 12 weeks. For patients with spinocerebellar degeneration, thyrotropin-releasing hormone possibly improves some ataxia signs over 10 to 14 days (1 Class II study). For patients with SCA type 3 who are ambulatory, lithium probably does not improve signs of ataxia over 48 weeks (1 Class I study). For patients with Friedreich ataxia, deferiprone possibly worsens ataxia signs over 6 months (1 Class II study). Data are insufficient to support or refute the use of numerous agents. For nonpharmacologic options, in patients with degenerative ataxias, 4-week inpatient rehabilitation probably improves ataxia and function (1 Class I study); transcranial magnetic stimulation possibly improves cerebellar motor signs at 21 days (1 Class II study). For patients with multiple sclerosis–associated ataxia, the addition of pressure splints possibly has no additional benefit compared with neuromuscular rehabilitation alone (1 Class II study). Data are insufficient to support or refute use of stochastic whole-body vibration therapy (1 Class III study).